?FLUID BALANCE IN CYCLING RATS AND OVARIECTOMIZED RATS TREATED WITH OESTRADIOL BENZOATE IN PHYSIOLOGICAL DOSES (50 JlglRAT) (Biological Sciences - PJSIR, 1995)
Plasma vasopressin concentrations have been shown to vary throughout the rat oestrus cycle. In order to deter- minehowthesefluctuationsinvasopressinarerelatedtofluidretention,studieshavebeencarriedoutinovariectomized female Sprague-Dawley rats injected subcutaneously daily witheither vehicle or oestradiol benzoate in physiological doses (50!lg/rat) for 14days. The animals were housed in individual metabolism cages under 12hr lightl12 hr dark regimen with free access to food and water. Urine samples, to determine volume, were obtained and food and water intake recorded at 8-9 and 17-18 hrs. in the oestradiol benzoate treated rats, food and water intake were reduced during both dark and light periods compared to the controls possibly due to the influence of elevated circulating oestradiol levels. Urine output showed a similar pattern oOfchanges which appeared to be related to the vasopressin concentrations. Plasma osmolality decreased in oestradiol benzoatetreated rats which was also correlated with the plasma vasopressin levels.The resultsof thisstudy indicatethat waterretention inoestradiol benzoate treated rats and oestradiol-induced increase in vasopressin may playa role in this fluid retention.